CAMPUR KODE KE DALAM GURU MATA PELAJARAN BAHASA INDONESIA SISWA KELAS VI SD NEGERI 07 KAMPUNG JAWA KOTA SOLOK - Elan Halid Elan Halid (Inovasi Pendidikan, 2018)
This research is motivated in the teaching and learning process, the teacher uses Indonesian as the language of instruction, but there are also teachers who use the local language. Conditions like this will cause language symptoms such as code mixing. Indonesian is used as an official language of instruction, while Minang language is used to adapt to the local languages that students often use. As a result of the use of two languages by the teacher who taught Indonesian at the 07 Kampung Jawa Elementary School in Solok City, linguistically or in language studies there was mixed code. The purpose of this study is to describe the mixed code into the Indonesian language subject teachers at SD Negeri 07 Kampung Jawa, Solok City. This type of research is qualitative with descriptive method. The object of this research is the homeroom teacher who teaches Indonesian at 07 Kampung Jawa Elementary School, Solok City. The results of this study are a form of mixed teacher speech code in the teaching and learning process and the causes of code mixing. The mixed form of code found is mixing code into 44 data. The language element used is Minangkabau or regional languages. This shows that code mixing occurs in formal situations such as in teaching and learning interactions. Teachers and students are expected to use Indonesian language that is good and true in the teaching and learning process. The use of Indonesian language that is good and right by the teacher will affect the use of the language of students. Thus, students will be easy and accustomed to using Indonesian in teaching and learning interactions and in various other formal situations. Keywords: Sociolinguistics, mixed code into, and cause of code mixing.